Estudo das propriedades mecânicas em diferentes temperaturas do pet e ensaios de arrancamento com tratamento mecânico em matriz cimentícia a base de cimento portland - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The aim of this search is to analyze the mechanical properties of polyethylene terephthalate, aiming at the production process of fibers with superficial and thermal mechanical treatments for use in various branches of civil engineering. The methodology applied to this study consisted of mechanical and microscopy tests, following the following steps: characterization of the materials used; Production of PET fiber; Surface and thermal mechanical treatments; Traction test; Pullout test; And surface scanning by scanning electron microscopy. In the heat treatment, temperatures were analyzed, in which the PET samples were exposed for a period of 60 minutes, for a further direct traction test. The best results for the tensile strength test were the temperature of 40 ° C and the deformation was the temperature of 180 ° C. In relation to the superficial mechanical treatment, the samples showed superior pullout strength with an increase of 115.77% and 102.17% for the age of 3 days and 7 days, respectively, compared to samples without treatment. In the microscopy the possible relationship between the lamination of the samples and the loss of tensile strength was verified, thus guaranteeing the ideal temperatures for the use of the fibers, increasing the range of uses of recycled elements in the civil construction.
Keywords: Engenharia civil; Fibras de PET; Politereftalato de etileno reciclado; Propriedades mecânica; Civil engineering; PET fibers; Mechanical properties; Recycled polyterephthalate ethylene; CNPQ::ENGENHARIAS